High-entropy shape memory alloy and preparation method thereof
The high-entropy shape memory alloy powder was prepared by ball milling, and the steps of pre-pressure drying and discharge plasma sintering were adopted to solve the problems of uneven composition and segregation in the traditional preparation method, and the high hardness and fracture strength of the high-entropy shape memory alloy were achieved.
Patent Information
- Application Number
- CN202510037276.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-03-25
AI Technical Summary
The preparation method of traditional high-entropy shape memory alloys has problems of uneven composition and segregation, which seriously affects the alloy performance.
The ball milling method is used to prepare high-entropy shape memory alloy powder, and the high-entropy shape memory alloy sintered body is formed through pre-pressure drying and discharge plasma sintering.
While taking into account the shape memory performance, the hardness and fracture strength of the alloy are improved, and the mechanical properties are significantly improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal materials, and in particular to a high entropy shape memory alloy and a preparation method thereof. Background Art
[0002] High entropy shape memory alloys have a shape memory effect, which allows them to deform at low temperatures, and then eliminate the deformation when heated, restoring the shape before deformation. For such alloys, people use mechanical processing and aging treatment methods to process the prepared alloys in the hope of changing the microstructure inside the alloy, thereby further improving the functional properties of the alloy. However, traditional alloys believe that too many component designs will produce many microstructures such as intermetallic compounds inside the alloy, resulting in poor processing performance of the alloy and making it more difficult to analyze the internal structure. Therefore, the definition of high entropy shape memory alloys is proposed by combining the four major effects of high entropy alloys with the concept of shape memory alloys. This type of alloy is proposed to solve the problem of fatigue and performance degradation of alloys caused by irreversible plastic deformation in shape memory alloys. The excellent performance of high entropy alloys in mechanical properties such as hardness and yield strength, as well as the existence of solid solution strengthening effect and diffusion retardation effect of this alloy, can effectively resist the plastic deformation of the alloy.
[0003] In recent years, high entropy shape memory alloys have attracted more and more attention from material researchers. At present, the traditional preparation method of high entropy shape memory alloys is mainly vacuum melting. However, when the boiling points of individual elements in some formulas are close to or lower than other elements, the volatilization of low-boiling-point elements during the melting process is difficult to control, which makes the traditional melting method subject to varying degrees of restrictions. In addition, this method has certain defects, such as uneven alloy composition, easy to cause composition segregation and other problems, the existence of these problems will have a very serious impact on the performance of the alloy. Summary of the invention
[0004] The main purpose of the present invention is to provide a high entropy shape memory alloy and a preparation method thereof, which have great advantages in mechanical properties compared with traditional alloys while taking into account shape memory properties.
[0005] In order to solve the above technical problems, the present invention discloses a high entropy shape memory alloy, and the chemical composition mass percentage of the high entropy shape memory alloy is: iron powder 15~25 wt.%, cobalt powder 18~25 wt.%, nickel powder 18~30wt.%, manganese powder 15~25wt.%, and titanium powder 8~25 wt.%.
[0006] According to one embodiment of the present invention, all of the above-mentioned raw material powders are single-substance powders with a purity greater than 99%: the particle size of the metal single-substance powder is 1-80 μm.
[0007] According to one embodiment of the present invention, the method for preparing the high entropy shape memory alloy comprises the following steps: (1) Preparation of high entropy shape memory alloy powder Iron powder, cobalt powder, nickel powder, manganese powder and titanium powder were put into a ball mill for ball milling. The mass ratio of ball to material was 5:1. The grinding balls were large and small stainless steel balls (diameters were 10 mm and 6 mm, respectively). The mass ratio of large and small balls was 6:4. The speed was set at 250-450 r / min. The machine was operated alternately. The machine was stopped for 30 min every 1 h. The cumulative ball milling time was 20-40 h. Then, the alloy bonded to the bottom of the ball mill was manually crushed in a glove box. During the ball milling process, a process control agent was dripped every 10 h. The control agent was industrial ethanol with a purity greater than 99.7%, and the dripping amount was 0.1-0.25 mL / g metal powder. After ball milling, the high entropy shape memory alloy powder was separated from the grinding balls in the glove box to obtain the high entropy shape memory alloy powder. (2) Pre-pressing and drying After the mixed powder in step (1) is dried, it is loaded into a WC cemented carbide mold for pre-pressing at a pressure of 100-400 MPa and a holding time of 30-60 s, and then the pre-pressed powder is dried at 50 °C for 2-5 h; (3) Spark plasma sintering The pre-pressed powder of step (2) is loaded into a graphite mold, and then spark plasma sintering is performed. The sintering pressure is set to 20-50 MPa, and the vacuum degree is 20 Pa before the furnace temperature reaches 400 °C. After the furnace temperature is heated to 450 °C, a protective Ar atmosphere is introduced, and the heating system is as follows: keep the temperature at 450 °C for 5-30 min, and then increase the temperature to a temperature close to the target temperature at a heating rate of 20-50 °C / min. When the set sintering temperature of 950-1100 °C is reached, keep the temperature for 5-10 min to obtain a high entropy shape memory alloy sintered body; (4) Grinding and polishing The surface of the sintered body prepared in step (3) is ground and polished to remove the graphite remaining on the surface of the sample sintered body and the burrs generated on the edge during the sintering process, thereby obtaining a high entropy shape memory alloy material.
[0008] Compared with the prior art, the present application can obtain the following technical effects: 1) The prepared high entropy shape memory alloy sintered body has better hardness and fracture strength while taking into account the shape memory performance.
[0009] Of course, any product implementing the present invention does not necessarily need to achieve all of the above technical effects at the same time. DETAILED DESCRIPTION
[0010] The following will explain the implementation methods of the present application in detail with reference to examples, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.
[0011] A high entropy shape memory alloy, wherein the chemical components of the high entropy shape memory are as follows: 15-25 wt.% of iron powder, 18-25 wt.% of cobalt powder, 18-30 wt.% of nickel powder, 15-25 wt.% of manganese powder, and 8-25 wt.% of titanium powder.
[0012] Furthermore, all raw material powders are elemental powders with a purity greater than 99%: the particle size of the metal elemental powder is 1~80 μm.
[0013] Furthermore, the preparation method of the high entropy shape memory alloy comprises the following steps: (1) Preparation of high entropy shape memory alloy powder Iron powder, cobalt powder, nickel powder, manganese powder and titanium powder were put into a ball mill for ball milling. The mass ratio of ball to material was 5:1. The grinding balls were large and small stainless steel balls (diameters were 10 mm and 6 mm, respectively). The mass ratio of large and small balls was 6:4. The speed was set at 250-450 r / min. The machine was operated alternately. The machine was stopped for 30 min every 1 h. The cumulative ball milling time was 20-40 h. Then, the alloy bonded to the bottom of the ball mill was manually crushed in a glove box. During the ball milling process, a process control agent was dripped every 10 h. The control agent was industrial ethanol with a purity greater than 99.7%, and the dripping amount was 0.1-0.25 mL / g metal powder. After ball milling, the high entropy shape memory alloy powder was separated from the grinding balls in the glove box to obtain the high entropy shape memory alloy powder. (2) Pre-pressing and drying After the mixed powder in step (1) is dried, it is loaded into a WC cemented carbide mold for pre-pressing at a pressure of 100-400 MPa and a holding time of 30-60 s, and then the pre-pressed powder is dried at 50 °C for 2-5 h; (3) Spark plasma sintering The pre-pressed powder of step (2) is loaded into a graphite mold, and then spark plasma sintering is performed. The sintering pressure is set to 20-50 MPa, and the vacuum degree is 20 Pa before the furnace temperature reaches 400 °C. After the furnace temperature is heated to 450 °C, a protective Ar atmosphere is introduced, and the heating system is as follows: keep the temperature at 450 °C for 5-30 min, and then increase the temperature to a temperature close to the target temperature at a heating rate of 20-50 °C / min. When the set sintering temperature of 950-1100 °C is reached, keep the temperature for 5-10 min to obtain a high entropy shape memory alloy sintered body; (4) Grinding and polishing The surface of the sintered body prepared in step (3) is ground and polished to remove the graphite remaining on the surface of the sample sintered body and the burrs generated on the edge during the sintering process, thereby obtaining a high entropy shape memory alloy material.
[0014] Therefore, 6 groups of examples with different proportions were carried out according to the above method. Example 1
[0015] By mass percentage, iron powder is 22.13 wt.%, cobalt powder is 23.35 wt.%, nickel powder is 23.26 wt.%, manganese powder is 21.77wt.%, and titanium powder is 9.49 wt.%. Put it in a stainless steel ball mill, the purity of all metal powders is greater than 99%, the particle size of the metal element powder is: iron powder 48 μm, cobalt powder 25 μm, nickel powder 1-3 μm, manganese powder 75 μm, titanium powder 48-75 μm, the ball-to-material ratio is 5:1, the ball milling medium is stainless steel balls, and after repeated gas washing (argon gas) in the transition chamber of the glove box, put it into the operation chamber, cover it with a sealing cover, and ensure that the argon environment in the tank is taken out and put into the ball mill. The ball milling speed is 400 r / min, and the forward and reverse rotations are alternately operated. Forward rotation is 1 h and stopped for 30 min, and then reversed for 1 h, and the cycle is repeated. The control agent is dripped every 10 h. The control agent is industrial ethanol (purity ≥99.7%), and the dripping amount is 0.2 ml / 10 g powder. After ball milling for 40 h, all the powder is taken out.
[0016] The mechanically alloyed high entropy shape memory alloy powder was loaded into a graphite mold pre-loaded with graphite pad paper, and pre-pressed by a hydraulic press at a pressure of 400 MPa for 60 s. The pre-pressed powder was then dried at 50 °C for 2 h. The obtained prefabricated sample was placed in a spark plasma sintering furnace for sintering experiments. The sintering pressure was set to 40 MPa and the sintering temperature was 1050 °C. The vacuum degree was 20 Pa before the furnace temperature reached 400 °C. After the furnace temperature was heated to 450 °C, a protective Ar atmosphere was introduced. The heating system was as follows: keep at 450 °C for 5 min, then heat at a rate of 50 °C / min to a temperature close to the target temperature, keep the temperature and pressure for 10 min, then unload the pressure and slowly cool to room temperature to obtain a high entropy shape memory alloy bulk material.
[0017] After the obtained high entropy shape memory alloy block material was polished, the organization and performance were tested using instruments used in conventional testing methods. The obtained technical parameters are as follows:
[0018] The prepared high entropy shape memory alloy has great advantages in mechanical properties compared with traditional alloys while taking into account the shape memory performance. Example 2
[0019] By mass percentage, iron powder is 20.21 wt.%, cobalt powder is 21.33 wt.%, nickel powder is 21.24 wt.%, manganese powder is 19.89wt.%, and titanium powder is 17.33 wt.%. Put it in a stainless steel ball mill, the purity of all metal powders is greater than 99%, the particle size of the metal element powder is: iron powder 48 μm, cobalt powder 25 μm, nickel powder 1-3 μm, manganese powder 75 μm, titanium powder 48-75 μm, the ball-to-material ratio is 5:1, the ball milling medium is stainless steel balls, and after repeated gas washing (argon gas) in the transition chamber of the glove box, put it into the operation chamber, cover it with a sealing cover, and ensure that the argon environment in the tank is taken out and put into the ball mill. The ball milling speed is 400 r / min, and the forward and reverse rotations are alternately operated. Forward rotation is 1 h and stopped for 30 min, and then reversed for 1 h, and the cycle is repeated. The control agent is dripped every 10 h. The control agent is industrial ethanol (purity ≥99.7%), and the dripping amount is 0.2 ml / 10 g powder. After ball milling for 40 h, all the powder is taken out.
[0020] The mechanically alloyed high entropy shape memory alloy powder was loaded into a graphite mold pre-loaded with graphite pad paper, and pre-pressed by a hydraulic press at a pressure of 400 MPa for 60 s. The pre-pressed powder was then dried at 50 °C for 2 h. The obtained prefabricated sample was placed in a spark plasma sintering furnace for sintering experiments. The sintering pressure was set to 40 MPa and the sintering temperature was 1050 °C. The vacuum degree was 20 Pa before the furnace temperature reached 400 °C. After the furnace temperature was heated to 450 °C, a protective Ar atmosphere was introduced. The heating system was as follows: keep at 450 °C for 5 min, then heat at a rate of 50 °C / min to a temperature close to the target temperature, keep the temperature and pressure for 10 min, then unload the pressure and slowly cool to room temperature to obtain a high entropy shape memory alloy bulk material.
[0021] After the obtained high entropy shape memory alloy block material was polished, the organization and performance were tested using instruments used in conventional testing methods. The obtained technical parameters are as follows:
[0022] The prepared high entropy shape memory alloy has great advantages in mechanical properties compared with traditional alloys while taking into account the shape memory performance. Example 3
[0023] By mass percentage, iron powder is 19.12 wt.%, cobalt powder is 20.18 wt.%, nickel powder is 20.09 wt.%, manganese powder is 18.81 wt.%, and titanium powder is 21.8 wt.%. Put it in a stainless steel ball mill, the purity of all metal powders is greater than 99%, the particle size of the metal element powder is: iron powder 48 μm, cobalt powder 25 μm, nickel powder 1-3 μm, manganese powder 75 μm, titanium powder 48-75 μm, the ball-to-material ratio is 5:1, the ball milling medium is stainless steel balls, and after repeated gas washing (argon gas) in the transition chamber of the glove box, put it into the operation chamber, cover it with a sealing cover, and ensure that the argon environment in the tank is taken out and put into the ball mill. The ball milling speed is 400 r / min, and the forward and reverse rotations are alternately operated. Forward rotation is 1 h and stopped for 30 min, and then reversed for 1 h, and the cycle is repeated. The control agent is dripped every 10 h. The control agent is industrial ethanol (purity ≥99.7%), and the dripping amount is 0.2 ml / 10 g powder. After ball milling for 40 h, all the powder is taken out.
[0024] The mechanically alloyed high entropy shape memory alloy powder was loaded into a graphite mold pre-loaded with graphite pad paper, and pre-pressed by a hydraulic press at a pressure of 400 MPa for 60 s. The pre-pressed powder was then dried at 50 °C for 2 h. The obtained prefabricated sample was placed in a spark plasma sintering furnace for sintering experiments. The sintering pressure was set to 40 MPa and the sintering temperature was 1050 °C. The vacuum degree was 20 Pa before the furnace temperature reached 400 °C. After the furnace temperature was heated to 450 °C, a protective Ar atmosphere was introduced. The heating system was as follows: keep at 450 °C for 5 min, then heat at a rate of 50 °C / min to a temperature close to the target temperature, keep the temperature and pressure for 10 min, then unload the pressure and slowly cool to room temperature to obtain a high entropy shape memory alloy bulk material.
[0025] After the obtained high entropy shape memory alloy block material was polished, the organization and performance were tested using instruments used in conventional testing methods. The obtained technical parameters are as follows:
[0026] The mechanical properties of the prepared high-entropy shape memory alloy have great advantages over traditional alloys. Example 4
[0027] By mass percentage, iron powder is 18.89 wt.%, cobalt powder is 19.93 wt.%, nickel powder is 26.41 wt.%, manganese powder is 18.85wt.%, and titanium powder is 16.19 wt.%. Put it in a stainless steel ball mill, the purity of all metal powders is greater than 99%, the particle size of the metal element powder is: iron powder 48 μm, cobalt powder 25 μm, nickel powder 1-3 μm, manganese powder 75 μm, titanium powder 48-75 μm, the ball-to-material ratio is 5:1, the ball milling medium is stainless steel balls, and after repeated gas washing (argon gas) in the transition chamber of the glove box, put it into the operation chamber, cover it with a sealing cover, and ensure that the argon environment in the tank is taken out and put into the ball mill. The ball milling speed is 400 r / min, and the forward and reverse rotations are alternately operated. Forward rotation is 1 h and stopped for 30 min, and then reversed for 1 h, and the cycle is repeated. The control agent is dripped every 10 h. The control agent is industrial ethanol (purity ≥99.7%), and the dripping amount is 0.2 ml / 10 g powder. After ball milling for 40 h, all the powder is taken out.
[0028] The mechanically alloyed high entropy shape memory alloy powder was loaded into a graphite mold pre-loaded with graphite pad paper, and pre-pressed by a hydraulic press at a pressure of 400 MPa for 60 s. The pre-pressed powder was then dried at 50 °C for 2 h. The obtained prefabricated sample was placed in a spark plasma sintering furnace for sintering experiments. The sintering pressure was set to 40 MPa and the sintering temperature was 1050 °C. The vacuum degree was 20 Pa before the furnace temperature reached 400 °C. After the furnace temperature was heated to 450 °C, a protective Ar atmosphere was introduced. The heating system was as follows: keep at 450 °C for 5 min, then heat at a rate of 50 °C / min to a temperature close to the target temperature, keep the temperature and pressure for 10 min, then unload the pressure and slowly cool to room temperature to obtain a high entropy shape memory alloy bulk material.
[0029] After the obtained high entropy shape memory alloy block material was polished, the organization and performance were tested using instruments used in conventional testing methods. The obtained technical parameters are as follows:
[0030] The prepared high entropy shape memory alloy has great advantages in mechanical properties compared with traditional alloys while taking into account the shape memory performance. Example 5
[0031] By mass percentage, iron powder is 22.13 wt.%, cobalt powder is 23.35 wt.%, nickel powder is 23.26 wt.%, manganese powder is 21.77wt.%, and titanium powder is 9.49 wt.%. Put it in a stainless steel ball mill, the purity of all metal powders is greater than 99%, the particle size of the metal element powder is: iron powder 48 μm, cobalt powder 25 μm, nickel powder 1-3 μm, manganese powder 75 μm, titanium powder 48-75 μm, the ball-to-material ratio is 5:1, the ball milling medium is stainless steel balls, and after repeated gas washing (argon gas) in the transition chamber of the glove box, put it into the operation chamber, cover it with a sealing cover, and ensure that the argon environment in the tank is taken out and put into the ball mill. The ball milling speed is 400 r / min, and the forward and reverse rotations are alternately operated. Forward rotation is 1 h and stopped for 30 min, and then reversed for 1 h, and the cycle is repeated. The control agent is dripped every 10 h. The control agent is industrial ethanol (purity ≥99.7%), and the dripping amount is 0.2 ml / 10 g powder. After ball milling for 40 h, all the powder is taken out.
[0032] The mechanically alloyed high entropy shape memory alloy powder was loaded into a graphite mold pre-loaded with graphite pad paper, and pre-pressed by a hydraulic press at a pressure of 400 MPa for 60 s. The pre-pressed powder was then dried at 50 °C for 2 h. The obtained prefabricated sample was placed in a spark plasma sintering furnace for sintering experiments. The sintering pressure was set to 40 MPa and the sintering temperature was 950 °C. The vacuum degree was 20 Pa before the furnace temperature reached 400 °C. After the furnace temperature was heated to 450 °C, a protective Ar atmosphere was introduced. The heating system was as follows: keep at 450 °C for 5 min, then increase the temperature to near the target temperature at a heating rate of 50 °C / min, keep the temperature and pressure for 10 min, then unload the pressure and slowly cool down to room temperature to obtain a high entropy shape memory alloy bulk material.
[0033] After the obtained high entropy shape memory alloy block material was polished, the organization and performance were tested using instruments used in conventional testing methods. The obtained technical parameters are as follows:
[0034] The prepared high entropy shape memory alloy has great advantages in mechanical properties compared with traditional alloys while taking into account the shape memory performance. Example 6
[0035] By mass percentage, iron powder is 22.13 wt.%, cobalt powder is 23.35 wt.%, nickel powder is 23.26 wt.%, manganese powder is 21.77wt.%, and titanium powder is 9.49 wt.%. Put it in a stainless steel ball mill, the purity of all metal powders is greater than 99%, the particle size of the metal element powder is: iron powder 48 μm, cobalt powder 25 μm, nickel powder 1-3 μm, manganese powder 75 μm, titanium powder 48-75 μm, the ball-to-material ratio is 5:1, the ball milling medium is stainless steel balls, and after repeated gas washing (argon gas) in the transition chamber of the glove box, put it into the operation chamber, cover it with a sealing cover, and ensure that the argon environment in the tank is taken out and put into the ball mill. The ball milling speed is 400 r / min, and the forward and reverse rotations are alternately operated. Forward rotation is 1 h and stopped for 30 min, and then reversed for 1 h, and the cycle is repeated. The control agent is dripped every 10 h. The control agent is industrial ethanol (purity ≥99.7%), and the dripping amount is 0.2 ml / 10 g powder. After ball milling for 40 h, all the powder is taken out.
[0036] The mechanically alloyed high entropy shape memory alloy powder was loaded into a graphite mold pre-loaded with graphite pad paper, and pre-pressed by a hydraulic press at a pressure of 400 MPa for 60 s. The pre-pressed powder was then dried at 50 °C for 2 h. The obtained prefabricated sample was placed in a spark plasma sintering furnace for sintering experiments. The sintering pressure was set to 40 MPa and the sintering temperature was 1150 °C. The vacuum degree was 20 Pa before the furnace temperature reached 400 °C. After the furnace temperature was heated to 450 °C, a protective Ar atmosphere was introduced. The heating system was as follows: keep the temperature at 450 °C for 5 min, then increase the temperature to a temperature close to the target temperature at a heating rate of 50 °C / min, keep the temperature and pressure for 10 min, then unload the pressure and slowly cool down to room temperature to obtain a high entropy shape memory alloy bulk material.
[0037] After the obtained high entropy shape memory alloy block material was polished, the organization and performance were tested using instruments used in conventional testing methods. The obtained technical parameters are as follows:
[0038] The mechanical properties of the prepared high-entropy shape memory alloy have great advantages over traditional alloys.
[0039] The above description shows and describes several preferred embodiments of the present application, but as before, it should be understood that the present application is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the present application through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present application, and shall be within the scope of protection of the claims attached to the present application.
Claims
1. A high entropy shape memory alloy, characterized in that: the mass percentage of the chemical components of the high entropy shape memory is: iron powder 15~25 wt.%, cobalt powder 18~25 wt.%, nickel powder 18~30 wt.%, manganese powder 15~25 wt.%, titanium powder 8~25 wt.%.
2. The high entropy shape memory alloy according to claim 1, characterized in that: All raw material powders are single-element powders with a purity greater than 99%: the particle size of metal single-element powders is 1~80 μm.
3. The method for preparing the high entropy shape memory alloy according to claim 1, comprising the following steps: (1) Preparation of high entropy shape memory alloy powder Iron powder, cobalt powder, nickel powder, manganese powder and titanium powder were put into a ball mill for ball milling, the mass ratio of ball to material was 5:1, the grinding balls were large and small stainless steel balls (diameters were 10 mm and 6 mm, respectively), the corresponding mass ratio of large and small balls was 6:4, the speed was set to 250-450 r / min, the operation was alternating, the machine was stopped for 30 min every 1 h, and the cumulative ball milling time was 20-40 h; then the alloy bonded to the bottom of the ball mill was manually crushed in a glove box, and a process control agent was dripped every 10 h during the ball milling process. The control agent was industrial ethanol with a purity greater than 99.7%, and the dripping amount was 0.1-0.25 mL / g metal powder; after ball milling, the high entropy shape memory alloy powder was separated from the grinding balls in the glove box to obtain the high entropy shape memory alloy powder; (2) Pre-pressing and drying After the mixed powder in step (1) is dried, it is loaded into a WC cemented carbide mold for pre-pressing at a pressure of 100-400 MPa and a holding time of 30-60 s, and then the pre-pressed powder is dried at 50 °C for 2-5 h; (3) Spark plasma sintering The pre-pressed powder of step (2) is loaded into a graphite mold, and then spark plasma sintering is performed. The sintering pressure is set to 20-50 MPa, and the vacuum degree is 20 Pa before the furnace temperature reaches 400 °C. After the furnace temperature is heated to 450 °C, a protective Ar atmosphere is introduced, and the heating system is as follows: keep the temperature at 450 °C for 5-30 min, and then increase the temperature to a temperature close to the target temperature at a heating rate of 20-50 °C / min. When the set sintering temperature of 950-1100 °C is reached, keep the temperature for 5-10 min to obtain a high entropy shape memory alloy sintered body; (4) Grinding and polishing The surface of the sintered body prepared in step (3) is ground and polished to remove the graphite remaining on the surface of the sample sintered body and the burrs generated on the edge during the sintering process, thereby obtaining a high entropy shape memory alloy material.